2015
DOI: 10.17511/ijphr.2015.i1.01
|View full text |Cite
|
Sign up to set email alerts
|

Ziabetus Shakari (Type 2 Diabetes Mellitus) in Elderly and its Dietary Management

Abstract: Prevalence of type 2 diabetes mellitus is increasing rapidly around the world. The ageing of the overall population is a significant driver of the diabetes epidemic. Diabetes in older adults is linked to higher mortality, reduced functional status, and increased risk of institutionalization. Nutrition is an integral part of diabetes care for all ages, but there are additional considerations for older adults with diabetes. The Unani system of medicine believes that a physician is not the healer but an assistant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Dietary habit was mixed in 41 (91.11%) patients and only 4 (8.88%) patients was pure vegetarian. Many clinical study-based data are available to suggest the relationship of diet with disease as observed by Jitendra et al [12] and Rowena et al [13] . Among 45 patients 26(57.8%) had positive family history of DM and 19 (42.2%) reported with no positive family history.…”
Section: Resultsmentioning
confidence: 99%
“…Dietary habit was mixed in 41 (91.11%) patients and only 4 (8.88%) patients was pure vegetarian. Many clinical study-based data are available to suggest the relationship of diet with disease as observed by Jitendra et al [12] and Rowena et al [13] . Among 45 patients 26(57.8%) had positive family history of DM and 19 (42.2%) reported with no positive family history.…”
Section: Resultsmentioning
confidence: 99%